Positive and negative cis-acting DNA domains are required for spatial and temporal regulation of gene expression by a seed storage protein promoter. - Bustos, M M (1991)
Mutations affecting spatial and temporal regulation of a beta-phaseolin gene encoding the major storage protein of bean (Phaseolus vulgaris) were analyzed by stable and transient transformation approaches. The results substantiate the value of transient assays for rapid determination of the functionality of cis-acting sequences and the importance of stable transformation to identify tissue-specific determinants. Spatial information is specified primarily by two upstream activating sequences (UAS). UAS1 (-295 to -109) was sufficient for seed-specific expression from both homologous and heterologous (CaMV 35S) promoters. In situ localization of GUS expression in tobacco embryos demonstrated that UAS1 activity was restricted to the cotyledons and shoot meristem. A second positive domain, UAS2 (-468 to -391), extended gene activity to the hypocotyl. Temporal control of GUS expression was found to involve two negative regulatory sequences, NRS1 (-391 to -295) and NRS2 (-518 to -418), as well as the positive domain UAS1. The deletion of either negative element caused premature onset of GUS expression. These findings indicate combinatorial interactions between multiple sequence motifs specifying spatial information, and provide the first example of the involvement of negative elements in the temporal control of gene expression in higher plants.